Evaluation of Salivary Mucin, Amylase, Protein Profile, and Periodontal Parameters among Hypertensive and Diabetic Patients - Madiha Anwar; Beenish F. Alam; Saqib Ali; Sahibzadi F. Tariq; Khalid Aali; Eisha Abrar; Dalal H. Alotaibi; Aljoharah A. Alsinaidi; Ali Alrahlah; Fahim Vohra (Applied Sciences, 2022)
Systemic and localized oral disease instigates alterations in salivary composition and content. The objective of the study was to evaluate the levels of salivary amylase, mucin, total protein levels, and periodontal inflammatory parameters in Type 2 Diabetes mellitus (T2DM), hypertensive (HTN) patients, and healthy controls. The study sample was divided into three groups: healthy, T2DM, and HTN. Salivary samples were collected from the included participants and salivary flow rate (SFR) and pH were measured. The salivary levels of amylase, mucin, and total protein concentration were analyzed using an enzyme-linked immunosorbent assay. The effect of anti-hypertensive and hypoglycemic drugs on the salivary flow rate, salivary pH, mucin, amylase, and total protein concentrations was evaluated. The results were analyzed with Chi-squared and analysis of variance to compare the means and standard deviations of variables among the study groups. SFR was significantly (p < 0.01) lower among diabetics (0.78 ± 0.45 mL/min) in comparison to healthy (1.52 ± 0.62 mL/min) and hypertensive (1.07 ± 0.7 mL/min) subjects. PISA values were significantly higher in T2DM (1029 ± 234.6 mm2) and HTN (799.4 ± 155.05 mm2) subjects when compared to controls, indicating a high inflammatory burden of oral cavity caused by these conditions, and showed statistically significant difference between the groups (p-value < 0.001). Mucin levels were significantly higher (p-value < 0.05) in hypertensive patients (4.6 ± 1.17 units) compared to diabetics (3.59 ± 1.03 unit/mL) and healthy (2.26 ± 1.09 units/mL) subjects. Amylase levels were significantly higher among healthy subjects (1.76 ± 0.75 mg/mL) compared to both hypertensive (1.33 ± 1.0 mg/mL) and diabetic (0.88 ± 0.57 mg/mL) patients. Total protein concentration was significantly raised (p-value < 0.001) in diabetics (37.67 ± 3.12 mg/mL) compared to healthy (29.3 ± 3.22 mg/mL) subjects. Significant differences in BOP, CAL, and PPD was observed (p-value < 0.001). Use of antihypertensive and hypoglycemic drugs showed a significant influence on salivary flow rate, protein, mucin, and amylase levels. T2DM and HTN induced irregularities in salivary flow rate, pH, amylase, and mucin levels and showed an increased incidence of moderate to severe periodontitis in patients. UWS levels of SFR, mucin, amylase, and total protein can be used as diagnostic and therapeutic biomarkers in patients with T2DM and HTN with oral disease.